Acute kidney disease is common and associated with poor outcomes in patients with cirrhosis and acute kidney injury - Patidar, Kavish R.; Naved, Mobasshir A.; Grama, Ananth; Adibuzzaman, Mohammad; Aziz Ali, Arzina; Slaven, James E.; Desai, Archita P.; Ghabril, Marwan S.; Nephew, Lauren; Chalasani, Naga; Orman, Eric S. (Journal of hepatology, 2022)
Acute kidney disease (AKD) is the persistence of acute kidney injury (AKI) for up to 3 months, which is proposed to be the time-window where critical interventions can be initiated to alter downstream outcomes of AKI. In cirrhosis, AKD and its impact on outcomes have been scantly investigated. We aimed to define the incidence and outcomes associated with AKD in a nationwide US cohort of hospitalized patients with cirrhosis and AKI. Hospitalized patients with cirrhosis and AKI in the Cerner-Health-Facts database from 1/2009-09/2017 (n = 6,250) were assessed for AKD and were followed-up for 180 days. AKI and AKD were defined based on KDIGO and ADQI AKD and renal recovery consensus criteria, respectively. The primary outcome measure was mortality, and the secondary outcome measure was de novo chronic kidney disease (CKD). Competing-risk multivariable models were used to determine the independent association of AKD with primary and secondary outcomes. AKD developed in 32% of our cohort. On multivariable competing-risk analysis adjusting for significant confounders, patients with AKD had higher risk of mortality at 90 (subdistribution hazard ratio [sHR] 1.37; 95% CI 1.14-1.66; p = 0.001) and 180 (sHR 1.37; 95% CI 1.14-1.64; p = 0.001) days. The incidence of de novo CKD was 37.5%: patients with AKD had higher rates of de novo CKD (64.0%) compared to patients without AKD (30.7%; p <0.001). After adjusting for confounders, AKD was independently associated with de novo CKD (sHR 2.52; 95% CI 2.01-3.15; p <0.001) on multivariable competing-risk analysis. AKD develops in 1 in 3 hospitalized patients with cirrhosis and AKI and it is associated with worse survival and de novo CKD. Interventions that target AKD may improve outcomes of patients with cirrhosis and AKI. In a nationwide US cohort of hospitalized patients with cirrhosis and acute kidney injury, acute kidney disease developed in 1 in 3 patients and was associated with worse survival and chronic kidney disease. Interventions that target acute kidney disease may improve outcomes of patients with cirrhosis and acute kidney injury. [Display omitted] •AKD develops in 1 in 3 patients with cirrhosis and AKI.•AKD is independently associated with worse 90- and 180-day survival.•AKD is independently associated with de novo chronic kidney disease.